Bulk- and single cell-RNA sequencing reveal KIF20A as a key driver of hepatocellular carcinoma progression and immune evasion - Su, Zhixiong; Zhong, Yaqi; He, Yufang; You, Lijie; Xin, Fuli; Wang, Lei; Liu, Zhihua (Frontiers in Immunology, 2024)
Kinesin family member 20A (KIF20A) is essential for cell proliferation and is implicated in promoting tumor progression, but its role in hepatocellular carcinoma (HCC) remains poorly studied.In this study, we firstly found KIF20A was overexprerssed in HCC both by bulk RNA-sequencing (bulk RNA-seq) and single-cell RNA sequencing (scRNA-seq), and then the overexpression of KIF20A significantly promoted the proliferation, invasion, and metastasis in vitro. In vivo, the overexpression of KIF20A promoted the growth and lung metastasis of HCC. Furthermore, gene set variation analysis of bulk RNA-seq and scRNA-seq revealed that KIF20A might be associated with cell cycle related signaling pathways of E2F and G2M, and overexpression of KIF20A inhibited the activity of p21 and bax, as well as shortened G2 phase. Importantly, we found that KIF20A could induce T cell exhaustion via the SPP1-CD44 axe using scRNA-seq. Additionally, KIF20A was also correlated with the expression of immune check-point inhibitors (ICIs), and KIF20Ahigh subgroup might be benefited from the ICIs therapy. Consequently, KIF20A emerges as a pivotal driver of HCC progression, intricately regulating cell cycle pathways and modulating immune responses, which position KIF20A as a promising target for HCC management.